(untitled) (Global Journal of Human-Social Science, 2012)
This study examines the relationship between the residents socio-economic status and their attitudes to the issue of security in their houses It surveys the housing environments in the different residential zones of Ogbomoso taking cognizance of physical devices adopted by residents for ensuring adequate protection of their lives and properties The physical security devices examined include the presence of a perimeter fence security gate security gatehouse and employment of security guard gateman The incidence employment and distribution of scores for these physical and human devices across the city are examined in relation to the socio-economic status of residents The result shows a high incidence of security personel devices among the residents with high socio-economic status found mostly in the lower density residential zones of the city and vise versa